Origins and global context of Brucella abortus in Italy. Issue 1 (December 2017) - Garofolo, Giuliano; Di Giannatale, Elisabetta; Platone, Ilenia; Zilli, Katiuscia; Sacchini, Lorena; Abass, Anna; Ancora, Massimo; Cammà, Cesare; Di Donato, Guido; De Massis, Fabrizio; Calistri, Paolo; Drees, Kevin; et al.
Abstract Background Brucellosis is a common and chronic disease of cattle and other bovids that often causes reproductive disorders. Natural infection in cattle is caused byBrucella abortus and transmission typically occurs during abortions, calving, or nursing. Brucellosis is also a major zoonotic disease due to contamination of dairy products or contact with the tissues of infected animals. Brucellosis has been eradicated from most of the developed world in the last 40 years but persists in many regions—the disease remains prevalent in portions of Africa, the Middle East, Asia, and Central and South America, as well as in the Mediterranean basin. In Italy, B. abortus has persisted in southern regions in both cattle and water buffalo. Previous attempts at analyzing the phylogenetics ofB. abortus in Italy have been challenging due to limited genetic variability and unresolved global population genetic structure of this pathogen. Results We conducted genome-wide phylogenetic analyses on 11 representative strains ofB. abortus from Italy, and compared these sequences to a worldwide collection of publically available genomes. Italian isolates belong to three clades that are basal to the main and globalB. abortus lineage. Using six SNP-based assays designed to identify substructure within the Italian clades, we surveyed a collection of 261 isolates and found that one clade predominates throughout endemic districts in the country, while the other two clades are more geographically restricted to portions of southern Italy. Conclusions Although related strains exist worldwide, B. abortus isolates from Italy are substantially different than those found in much of the rest of Europe and North America, and are more closely related to strains from the Middle East and Asia. Our assays targeting genetic substructure within Italy allowed us to identify the major lineages quickly and inexpensively, without having to generate whole genome sequences for a large isolate collection. These findings highlight the importance of genetic studies to assess the status and the history of pathogens.